The technique of craniospinal irradiation of paediatric patients in supine position - Šlampa, Pavel (Radiology and oncology (Ljubljana), 2001)
Background. Postoperative radiation therapy has significant impact on local control and overall survival of paediatric patients with brain tumours but an irradiated volume is often a controversial issue. Our aim was to describe a new technique of craniospinal irradiation as a postoperative treatment in patients with the risk of relapse of brain tumours as well as to estimate the side effects of such craniospinal irradiation. Patients and methods. In the last 4 years, 17 paediatric patients under 15 years of age with medulloblastoma (8) ependymoma (6) and glioblastoma (3) received postoperativecraniospinal axis radiotherapy by a new technique developed in our departments. This technique is based on irradiation in supine position with the use of asymmetric jaws of the linear accelerator. Results. Radiotherapy was well tolerated and dose-reduction was not needed in any case.Skin reactions were mild in all patients. The gastrointestinal and haematological toxicity was mild to moderate (WHO grade 1-II). Conclusion. Theproposed new technique of craniospinal irradiation is advantageous in termsof side effects and could be recommended to be widely used. Craniospinal irradiation in supine position is an alternative method to the treatment in prone position. The evaluation of the effectiveness was limited by a short follow-up interval.
Keywords: Brain neoplasms; Child; Hrbtna lega; Methods; možgani; Možgani, novotvorbe; obsevanje; otroci; Otrok; radiologija; Radioterapija; Radiotherapy; rak (medicina); Supine position; therapy; zdravljenje